THEORIES AND SUCCESS STORIES OF GREEN MARKETING - Wilardjo, Setia Budhi (VALUE ADDED | MAJALAH EKONOMI DAN BISNIS, 2011)
Green marketing is strategic process involving stakeholder assessment to create meaningful long-term relationship which customer while maintaining, supporting, and enhancing the natural environment. According to the American Marketing Association, green marketing is the marketing of products that are presumed to be environmentally safe. Green marketing subsumes greening products as well as greening firms. In addition to manipulating the 4Ps (product, price, place and promotion) of the traditional marketing mix, it requires a careful understanding of public policy processes. Environmentally friendly (also eco-friendly, nature friendly, and green) are terms used to refer to goods and services, laws, guidelines and policies claimed to inflict minimal or no harm on the environment.